John Dewey and Friedrich Nietzsche: Aesthetics of Life - Luque-Moya, Gloria (My University, 2014)
In 1934 John Dewey laid the foundation of a Philosophy of Art which try to restore the continuity between art and everyday life. Dewey asserted that aesthetics has its roots in the essential conditions of life, that is, the basic vital functions which human beings share with birds and beasts. Human beings are exposed to conflicts from its dynamic surroundings, and at every moment they try to restore the harmony, to create more meaningful ways of living. Not many years before, Friedrich Nietzsche developed a philosophy of art which was not interested in Fine Arts or in providing a traditional theory of art, but in art as a transformative and creative force. Although these authors never met each other and their thoughts seem to be quite different, both philosophers overcome modern aesthetics which considered art for art’s sake and stress the role of art because of its power to reevaluate human experience and their surroundings. The aim of this paper is to examine the thesis of life as an aesthetic process from a comparative approach to the views of these authors. This paper’s presentation explores two main points: the naturalistic background of aesthetics and the creative and dynamic role of art. I begin drawing a comparison between deweyan naturalistic humanism and nietzschean physiology of art. Both authors show the importance of nature and body to develop aesthetic experiences, however, they present several differences. In spite of the fact they share the emphasis in art as a conciliation between human beings and nature in their later works, they have different positions. Secondly, I would like to address fundamental similarities between the creative role of artist and human beings through Dewey’s notion of experience and Nietzsche’s conception of pulsional life (Triebleben). They offer a way of transforming philosophy from an aesthetic approach, which focus on the impulse of aesthetic world-making. Thus, I will try to explain how both authors share that living creatures develop a cumulative progression toward fulfillment experiences, which are not permanent constants, but variable and changed situations of creative process that constitutes our lives. Through this paper’s presentation, I wish to show how, despite the divergences, these proposals provide an overview of art’s creation which attempt to demonstrate the rich background of our lives from which we create art as a way of leading a meaningful life.
Keywords: Arte - Filosofía; Everyday Aesthetics; Experience; Will to power